1998
DOI: 10.1243/0954407981526145
|View full text |Cite
|
Sign up to set email alerts
|

Combustion analysis and cycle-by-cycle variations in spark ignition engine combustion Part 2: A new parameter for completeness of combustion and its use in modelling cycle-by-cycle variations in combustion

Abstract: This paper investigates a technique of calculating the completeness of combustion on a cycle- by-cycle basis. The technique introduces the normalized pressure rise due to the combustion parameter, ψ to describe the completeness of combustion. This parameter is based on the Rassweiler-Withrow method of calculating the mass fraction burned and is derived from the pressure-crank angle record of the engine. Experimental data were obtained from a Rover K4 optical access engine and analysed with a combustion analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…By comparing the two cases, it is observed that in lean operating conditions, the impact of the ignition timing on the indicated mean effective pressure is higher compared to the stoichiometric mixture, an observation which is in agreement with other studies [2][3][4][5][6][7][8][9]. From these data it seems that cycle-to-cycle combustion variability is more pronounced in lean and highly diluted mixtures, even with slight modification of the combustion parameters.…”
Section: Effect Of Engine Operation Parameters On Emissionssupporting
confidence: 88%
See 4 more Smart Citations
“…By comparing the two cases, it is observed that in lean operating conditions, the impact of the ignition timing on the indicated mean effective pressure is higher compared to the stoichiometric mixture, an observation which is in agreement with other studies [2][3][4][5][6][7][8][9]. From these data it seems that cycle-to-cycle combustion variability is more pronounced in lean and highly diluted mixtures, even with slight modification of the combustion parameters.…”
Section: Effect Of Engine Operation Parameters On Emissionssupporting
confidence: 88%
“…In most CCV analysis, only the thermodynamic data are measured, without considering the emission data. Ball et al (1998) [4] used experimental data from a Rover K4 optical engine to investigate cycle-to-cycle variation in combustion and NO emissions. The fuel used in those experiments was methane.…”
Section: Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations